2014
DOI: 10.1039/c4ta04247f
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar anodization enables the fabrication of controlled arrays of TiO2 nanotube gradients

Abstract: We report here a new concept, the use of bipolar electrochemistry, which allows the rapid and wireless growth of self-assembled TiO 2 NT layers that consist of highly defined and controllable gradients in NT length and diameter. The gradient height and slope can be easily tailored with the time of electrolysis and the applied electric field, respectively. As this technique allows obtaining in one run a wide range of self-ordered TiO 2 NT dimensions, it provides the basis for rapid screening of TiO 2 NT propert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 36 publications
3
80
0
Order By: Relevance
“…For comparison, tubes with a length and an aspect ratio of ~44 µm / ~317, and ~56 µm / ~337 were observed after an additional 1 hour at 100 V, reached with a sweep rate of 1 V/s and 10 mV/s, respectively. This shows that the nanotubes were growing faster at higher potentials, in line with Figure 4, and previous literature [38][39][40][41][42].…”
Section: Influence Of the Electrolyte Age On The Nanotube Diameter Ansupporting
confidence: 79%
See 3 more Smart Citations
“…For comparison, tubes with a length and an aspect ratio of ~44 µm / ~317, and ~56 µm / ~337 were observed after an additional 1 hour at 100 V, reached with a sweep rate of 1 V/s and 10 mV/s, respectively. This shows that the nanotubes were growing faster at higher potentials, in line with Figure 4, and previous literature [38][39][40][41][42].…”
Section: Influence Of the Electrolyte Age On The Nanotube Diameter Ansupporting
confidence: 79%
“…Subsequently the IR drop becomes lower for older electrolytes and the real potential on the working electrode increased. Since the diameter of the nanotubes strongly depends on the applied potential [38][39][40][41][42][43]46], the diameter of the tubes increased with increasing age of the electrolytes. Evidently, the electrolyte can actually be used several times without any significant issues of lower quality.…”
Section: Influence Of the Electrolyte Age On The Nanotube Diameter Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it has been reported that the nanotube dimensions (e.g., diameter and length) strongly influence their physicochemical properties, [21] fabrication and studies of the TiO 2 nanotube array thin films with size gradients have so far received relatively little attention [22][23][24]. The previous work in which TiO 2 nanotube size gradients were used to rapid screen the tube length dependence with respect to the photoelectrochemical properties clearly constitutes significant progress, [25] even though a small fraction of the nanotubes (i.e., the nanotubes with the optimal length) provided the majority of the photoelectrochemical effects. In the case of energy storage materials, it can be anticipated that the possibility to carefully control and alter the gradients (and the sizes of individual nanotubes within the gradients) would prove even more advantageous.…”
Section: Introductionmentioning
confidence: 99%